International Integration, Democracy and Information Security of the State - Viktor Petrovich Kirilenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Information security of the state in the socio-political sphere is provided by state authorities and the national media. Democratic processes and international integration depend on a proper understanding of peoples social policy purposes in the universal scale. Information security of the state under democratic conditions requires a clear national policy reflecting its results and advantages in the world media.